Sex differences in heart rate and heart rate variability in rats: Implications for translational research - Carnevali, Luca; Barbetti, Margherita; Statello, Rosario; Williams, DeWayne P.; Thayer, Julian F.; Sgoifo, Andrea (Frontiers in Physiology, 2023)
The present study aimed to investigate sex differences in measures of cardiac chronotropy and heart rate variability (HRV) in 132 young adult wild-type Groningen rats (n = 45 females). Electrocardiographic signals were recorded for 48 hours in freely moving rats to quantify heart rate (HR) and inter-beat interval (IBI) as measures of cardiac chronotropy, and time- and frequency-domain HRV parameters as physiological readouts of cardiac vagal modulation. Females showed greater vagally-mediated HRV despite having higher HR and shorter IBI than males during undisturbed conditions. Such differences were evident (i) at any given level of HRV, and (ii) both during the 12-h light/inactive and 12-h dark/active phase of the daily cycle. These findings replicate the paradoxical cardiac chronotropic control reported by human meta-analytic findings, since one would expect greater vagally-mediated HRV to be associated with lower HR and longer IBI. Lastly, the association between some HRV measures and HR was stronger in female than male rats. Overall, the current study in young adult rats provides data illustrating a sex-dependent association between vagally-mediated HRV and indexes of cardiac chronotropy. The current results (i) are in line with human findings, (ii) suggest to always consider biological sex in the analysis and interpretation of HRV data in rats, and (iii) warrant the use of rats for investigating the neuro-hormonal basis and temporal evolution of the impact of sex on the association between vagally-mediated HRV and cardiac chronotropy, which could inform the human condition.